Reaktualisasi Kecerdasan Moral dan Keadaban Warga Negara - Sumaryati Sumaryati (Society, 2024)
Civilized citizens are very important for the state’s existence, especially in the era of globalization, where participation, obedience to norms, concern, and responsibility are needed to strengthen the state. However, some citizens are still less civilized, such as aggressive, emotional, apathetic, and violating norms. This shows the importance of balance between intellectual and moral intelligence. The study explores moral intelligence, the reactualization of moral intelligence, and its relationship to citizen civilization. The method used is a literature study on moral intelligence and its strengthening. The steps of the study include identification, content review, classification, and data analysis. The reactualization of moral intelligence is carried out by implementing seven main virtues: strengthening moral reasoning, improving the system, and continuing moral training. Moral training is a method of reactualizing moral intelligence by habituating the seven virtues of pleasant moral intelligence—implications of moral training in character education policies based on school culture and community-based.